Steepest Ascent Hill Climbing Algorithm To Solve Cases In Puzzle Game 8 - S Silvilestari (IJISTECH (International Journal of Information System and Technology), 2021)
The 8th puzzle compiling game is part of searching. Puzzle 8 is an implementation of the steepest ascent hill climbing algorithm by following the established rules. The working process of this algorithm is by looking at the initial position of the puzzle arrangement, after carrying out the process, the results of the shift are seen, whether it is approaching the correct arrangement position. The problem that often occurs is the lack of knowledge in solving game cases quickly so that it takes a long time to obtain the final state. The main purpose of this study is to provide information so that it is easy to solve puzzle game cases using an algorithm. The final result is a puzzle arrangement that is in accordance with the rules by using the concept of an algorithm so as to obtain a decision-making system to complete the puzzle game correctly.